2016
DOI: 10.15171/jcvtr.2016.25
|View full text |Cite
|
Sign up to set email alerts
|

Study of the normal heart size in Northwest part of Iranian population: a cadaveric study

Abstract: Introduction: The heart is in a muscular organ in the middle mediastinum. According to our knowledge, there is no standard data about the anthropologic parameters of normal Iranian hearts. Hence, the aim of the present study was to investigate the normal heart size in Iranian cadavers. Methods: In a cross-sectional study, 550 cadavers (104 female/446 male) from June 2014 to July 2015 in the Razavi Khorasan province of Iran were included in the study. After approval of the Ethical Committee, cadavers were divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…According to Gray's Anatomy, the heart length and width are 12 cm and 8.5 cm [12]. More recently, length and width have been investigated in different age groups in the Iranian population, with mean values of 11.41 ± 2.15 cm and 8.21 ± 4.38 cm, respectively [23].…”
Section: Definition Of Normal Heart In Relation To Hypertrophymentioning
confidence: 99%
“…According to Gray's Anatomy, the heart length and width are 12 cm and 8.5 cm [12]. More recently, length and width have been investigated in different age groups in the Iranian population, with mean values of 11.41 ± 2.15 cm and 8.21 ± 4.38 cm, respectively [23].…”
Section: Definition Of Normal Heart In Relation To Hypertrophymentioning
confidence: 99%
“…The 2 nd most common tricuspid circumference was between 8.5 -9.5 cm (20 %) which was also reported by some other observer, 24 while the values obtained by some authors were found to be higher. 11,27 The difference in these values could be because of the different method applied by them where they used the image J software.…”
Section: Dimensions Of Tricuspid Valvementioning
confidence: 99%
“…This type of anthropometric data are a prerequisite for the accurate interpretation of echocardiography, ante-mortem and post-mortem cardiac MRI and CT [10][11][12], surgical reconstruction and repair of the heart and valves [18,19] and interpretation of cardiac measurements in pathological and medico-legal autopsies. There appears to be a geographical/racial variation on the norms of measurements for the heart and it was proven in most of the studies done in other countries [20][21][22] as well as in Sri Lanka [18,19]. Data on normal cardiac anthropometric measurements for the Sri Lankan population are scarce and scanty.…”
Section: Discussionmentioning
confidence: 99%